DISTÚRBIOS RESPIRATÓRIOS DO SONO E PERFIL CLÍNICO EM INDIVÍDUOS COM DIABETES MELLITUS TIPO 2 - Fontela, Paula C.; Pretto, Luciana M.; Winkelmann, Eliane R.; Berlezi, Evelise M. (Salão do Conhecimento, 2013)
Resumo